2021
DOI: 10.1177/09574565211052693
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise models and noise guidelines: A review

Abstract: Traffic noise is a major cause of noise pollution, and impacts of noise pollution on humans have been studied extensively. Previous studies have helped in the development of traffic noise prediction analysis using robust analytical and computational models, parameters connected with traffic, road characteristics, and environment. This study reviewed 11 traffic noise modeling strategies and parameters used by various agencies in different parts of the world. Seven out of the 11 models reviewed in this paper wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…It is generally considered to represent the background or ambient level of a noise environment. 7274…”
Section: Scenario Formulation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally considered to represent the background or ambient level of a noise environment. 7274…”
Section: Scenario Formulation and Discussionmentioning
confidence: 99%
“…When considering the assessment of traffic noise, noise measurement is required as the base process to determine the level of noise and its associated underlying factors. 76 From the measurements it was observed that the noise levels were above the permissible limit and as such cause annoyance, which may lead to other health related problems. The country, which is still developing and already faces economic difficulties, may be impacted by this, if not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model [4] was developed at the National Physics Laboratory in Sydney. During the measurement, the traffic was free, on a flat road, without traffic signals.…”
Section: Burgess Modelmentioning
confidence: 99%
“…In the context of this research, on-road noise (sound level) measurement for cyclists can serve several types of investigation. Noise exposure itself is an environmental hazard commonly targeted for mitigation in highway design ( 14 ), although adverse health effects from noise exposure during cycling specifically have not been established. Traffic noise is also a source of annoyance and discomfort, and noise exposure has been investigated with an interest in the effects on travel behavior ( 57 ).…”
mentioning
confidence: 99%